The Digital Divide As A Determinant Of Student Attainment At A Selected University In The Western Cape - Asoba, Samson Nambei; Mefi, Nteboheng Patricia (Journal of Ecohumanism, 2025)
Socio-economic inequalities in South Africa remain an issue of concern. While the country has made various initiatives to address this vice, it remains critical and a threat to the attainment of democracy. Another form of inequality related to technology access; use ad adoption has emerged in recent years and creating the digital divide. The purpose of this study was to explore the digital divide and its role in student attainment at higher education levels. The study adopted the quantitative research based on the Mann Whitney Test of independence to attain its objectives. Students from a class in the faculty of Business and Management Sciences at a University were split into two groups and given three hours to complete a 1000 page essay in Business Leadership. The first group of 45 students was allowed full access to digital systems in doing the assignment while the other group of 45 was confined to no access to technological and digital systems in doing the assignment. The marks were then compared using the Mann Whitney test of independence. The results of the study demonstrated significant difference between the scores of the two groups thereby suggesting that the digital divide has become a predictor of educational attainment in the digitalized higher education system. The government and other stakeholders in the education system are recommended to create policies and curriculum delivery systems that are sensitive to the digital divide.